COVID-19 Pandemic in a Vulnerable Population: Prevalence and Correlates of Anxiety - Reham Shalaby; Ejemai Eboreime; Nnamdi Nkire; Belinda Agyapong; Hannah Pazderka; Gloria Obuobi-Donkor; Medard Kofi Adu; Wanying Mao; Ernest Owusu; Folajinmi Oluwasina; Vincent I. O. Agyapong (Behavioral Sciences, 2022)
Background: The COVID-19 pandemic has produced negative mental health outcomes. These effects were more prominent in vulnerable communities that experienced prior similar disasters. The study aimed to examine the likelihood and correlates of anxiety symptoms among Fort McMurray (FMM) residents, during the COVID-19 pandemic. Methods: A cross-sectional online survey questionnaire was applied between 24 April and 2 June 2021, at FMM, to gather sociodemographic, COVID-19, and clinical information, including generalized anxiety disorder (using GAD-7 scale). Results: Overall, 186 individuals completed the survey (response rate 74.7%). Most of the respondents were females (159, 85.5%); above 40 years (98, 52.7%); employed (175, 94.1%); and in relationship (132, 71%). The prevalence of moderate-to-severe anxiety was (42.5%, 71) on GAD-7 self-reported scale. Subscribers who reported that they would like to receive mental health support; have received no family support since COVID-19 declaration; and have lost their job during the pandemic were all more likely to report moderate-to-severe anxiety (OR = 3.39; 95% CI: 1.29–8.88), (OR = 4.85; 95% CI: 1.56–15.03), and (OR = 4.40; 95% CI: 1.01–19.24), respectively. Conclusions: Anxiety levels were high among FMM residents, compared to levels before COVID-19. Clinical and social factors significantly predicted likely anxiety in the Fort McMurray population, during the COVID-19 pandemic. It is imperative that resources are mobilized to support vulnerable communities during the COVID-19 pandemic.